2012
DOI: 10.1371/journal.pone.0044605
|View full text |Cite
|
Sign up to set email alerts
|

An Exported Heat Shock Protein 40 Associates with Pathogenesis-Related Knobs in Plasmodium falciparum Infected Erythrocytes

Abstract: Cell surface structures termed knobs are one of the most important pathogenesis related protein complexes deployed by the malaria parasite Plasmodium falciparum at the surface of the infected erythrocyte. Despite their relevance to the disease, their structure, mechanisms of traffic and their process of assembly remain poorly understood. In this study, we have explored the possible role of a parasite-encoded Hsp40 class of chaperone, namely PFB0090c/PF3D7_0201800 (KAHsp40) in protein trafficking in the infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…15,27 Use of gene knockout mutants has revealed that in addition to KAHRP, 2 genes, those encoding a PHIST domain protein (PFD1170c) and an Hsp40-like DNAJ Type IV protein (PF10_0381), are also important for knob formation. 15 Other parasite proteins that have been shown to associate with knob components, and which may thus form part of the knob structure, include knob-associated Hsp40, 28 the PfEMP1 trafficking protein PfEMP3, 16,28 the large variable surface antigen SURFIN, 29 the 2.5 MDa Pf332 antigen, 30 and the PHIST domain protein PFE1605w (LyMP). 31,32 PFE1605w is localized at the cell periphery 33 and has been shown to be important for cytoadherence but not for knob formation or for surface expression of PfEMP1.…”
Section: Introductionmentioning
confidence: 99%
“…15,27 Use of gene knockout mutants has revealed that in addition to KAHRP, 2 genes, those encoding a PHIST domain protein (PFD1170c) and an Hsp40-like DNAJ Type IV protein (PF10_0381), are also important for knob formation. 15 Other parasite proteins that have been shown to associate with knob components, and which may thus form part of the knob structure, include knob-associated Hsp40, 28 the PfEMP1 trafficking protein PfEMP3, 16,28 the large variable surface antigen SURFIN, 29 the 2.5 MDa Pf332 antigen, 30 and the PHIST domain protein PFE1605w (LyMP). 31,32 PFE1605w is localized at the cell periphery 33 and has been shown to be important for cytoadherence but not for knob formation or for surface expression of PfEMP1.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to PFB0085c, disruption of PFB0090c, which has recently been shown to encode DnaJ domain-containing KAHsp40 (32,33), resulted in a marked reduction in expression of VAR2CSA and a negligible level of C4S-binding capacity in CS2 parasites (34). However, upon panning of PFB0090c-knock-out parasites on CSA-coated plates, C4S-adherent parasites were selected.…”
Section: Discussionmentioning
confidence: 99%
“…8). This is interesting, given that PFB0090c is a KAHsp40 chaperone, which interacts with knobassociated proteins, such as PfEMP1, KAHRP, and PfEPMP3, in addition to the chaperones, Hsp70 and Hsp101 (32,33). Thus, increased expression of PFB0090c could contribute at least partly to higher levels of VAR2CSA expression.…”
Section: Pfb0080c Plays a Role In The Expression Of Pfemp1 And Cytoadmentioning
confidence: 99%
See 2 more Smart Citations